Perfil hematológico de tilápias-do-nilo alimentadas com die-tas contendo diferentes lipídeos e estimuladas por baixa temperatura - Araujo, Daniel De Magalhães; Fernandes Junior, Ademir Calvo [UNESP]; Teixeira, Caroline Pelegrina [UNESP]; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP] (My University, 2015)
The goal of this paper was to determine the effects of seven diets with differents fatty acids sources in hematology of Nile tilapia before and after cold stimulus. Seven diets, with 3% of fatty acid source, were formulated: soybean oil (OS); fish oil (OP); beef tallow (SB) and mixtures of OS+OP; OS+SB; OP+SB e OS+OP+SB. Fish (112 male of Nile tilapia of 30,0 ± 2,65g) were totally randomly distributed, with four repli-cates, into 28 plastic aquaria (40 L; 4 fish per aquarium). Fish were fed four times per day for 35 days. At 35th day and also after seven days cold stimulus blood was collected and the profile hematological was evaluated. Leucocytes numbers were reduced in fish fed a SB and fish oil combination diet and were highest in fish fed SB diet before cold stimulus. Plasma protein was reduced in fish fed soybean oil diets and highest in fishes fed a combination of soybean oil, fish oil and SB diets. Anything fatty acids source promotes effective changes in fish health and cold tolerance promotion. Cold don’t drastically reduced fish general health status.
Hematological profile of Nile tilapia fed diets with different lipids and challenged by cold
Keywords: Fish health; Fish nutrition; Fish oil; Oreochromis niloticus; Soybean oil